Strengthening Character Education Through Implementation of The School Literacy Movement - Luma’ul ‘Adilah Hayya’; Aldy Prasetyo (Proceeding International Conference on Religion, Science and Education, 2023)
Not a few of today's young generation are experiencing moral and character degradation, especially elementary school children. The literacy movement is an alternative to helping strengthen character education in children. The purpose of this research is to describe the implementation of Character Education, to describe the implementation of the School Literacy Movement, and to describe the strategy for instilling character values in the implementation of the School Literacy Movement at MIN 3 Purbalingga. This research includes field research using a qualitative descriptive approach. The data collection methods used were interviews, observation, and documentation with the principal, the GLS team and students as the main informants. The data analysis technique uses the steps of data collection, data reduction, data presentation, data verification and conclusion drawing. The results of this research are firstly that character education at MIN 3 Purbalingga uses a multi-approach, namely a religious approach, a philosophical approach, a sociocultural approach, and a scientific approach; carried out with three processes, namely thinking, behaving, and doing. Second, the School Literacy Movement at MIN 3 Purbalingga is implemented through three stages, namely the preparation stage, which includes: coordination meetings, the formation of the GLS Team, the socialization of the GLS program, and the preparation of infrastructure, the implementation stage, includes: enjoyable reading habits to foster participants' interest in reading students, generate bills in a literacy results document that can be evaluated, and create literacy-based learning activities through coordination with each subject teacher, and the evaluation stage, includes evaluation of literacy results billing documents and evaluations at the level of students' liking for reading. The strategy of instilling character values in the implementation of the School Literacy Movement at MIN 3 Purbalingga is classified into three types of strategies, namely strategies for utilizing infrastructure, strategies for integrating the School Literacy Movement with the curriculum, and strategies for the process of literacy activities.